Knowledge Based Automated Topic Identification - Lin, Chin-Yew (33rd Annual Meeting of the Association for Computational Linguistics (ACL'95), 1995)
As the first step in an automated text summarization algorithm, this work presents a new method for automatically identifying the central ideas in a text based on a knowledge-based concept counting paradigm. To represent and generalize concepts, we use the hierarchical concept taxonomy WordNet. By setting appropriate cutoff values for such parameters as concept generality and child-to-parent frequency ratio, we control the amount and level of generality of concepts extracted from the text.